A STUDY OF MATHEMATICS LEARNING ACHIEVEMENT AND DISCIPLINE THROUGH THE FLIPPED CLASSROOM UNDER THE CONCEPT ACTIVE LEARNING APPROACH OF MATTHAYOMSUKSA THREE STUDENTS BANGKOK CHRISTIAN COLLEGE - Dumrongchayakul, Nithi; Sumirattana, Sunisa (Journal of MCU Nakhondhat, 2023)
The Objectives of this research were to 1) to compare the mathematics learning achievement of statistics among Matthayomsuksa Three students Bangkok Christian College, before and after the flipped classroom under the concept of the active learning approach; 2) to compare discipline among Matthayomsuksa Three students Bangkok Christian College before, and after the flipped classroom under the concept of the active learning approach. By using a Quasi-Experimental research methodology. The sample in this study consisted of one classroom of 41 Matthayomsuksa Three students in Bangkok Christian College school. The participants were chosen by cluster random sampling. The experiment lasted for fourteen periods. The following instruments were used in this research: (1) lesson plans using the flipped classroom under the concept of the active learning approach of statistics among Matthayomsuksa Three for 10 lesson plans; (2) a mathematics learning achievement test on statistics for Matthayomsuksa Three; and (3) a test for discipline. The data were analyzed using mean, standard deviation and analyzed through a t-test for dependent sample. The research findings were as follows: (1) The mathematics learning achievement of statistics among Matthayomsuksa Three students after the flipped classroom under the concept of the active learning approach were higher than before they started learning at a statistically significant level of .01; (2) discipline among Matthayomsuksa Three students after the flipped classroom under the concept of the active learning approach were higher than before they started learning at a statistically significant level of .01.